The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1126/sciadv.aba5032
|View full text |Cite
|
Sign up to set email alerts
|

Depolarizing GABA A current in the prefrontal cortex is linked with cognitive impairment in a mouse model relevant for schizophrenia

Abstract: Cognitive impairment in schizophrenia (CIAS) is the most critical predictor of functional outcome. Limited understanding of the cellular mechanisms of CIAS hampers development of more effective treatments. We found that in subchronic phencyclidine (scPCP)–treated mice, an animal model that mimics CIAS, the reversal potential of GABAA currents in pyramidal neurons of the infralimbic prefrontal cortex (ILC) shifts from hyperpolarizing to depolarizing, the result of increased expression of the chloride transporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 57 publications
(68 reference statements)
1
21
0
Order By: Relevance
“…The altered synaptic inputs may also cause a more general effect, which is a widespread alteration of the excitation/inhibition (E/I) balance. E/I imbalance is regarded as a key pathogenic mechanism in numerous neurodevelopmental disorders (Deidda et al, 2015;Kim et al, 2021). Thus, it is possible that through recurrent inhibitory and excitatory circuitries the mPFC network acts as a magnifier of the effects of even minor alterations in specific inputs, so that relatively minor synaptic changes end up producing large behavioral effects.…”
Section: Discussionmentioning
confidence: 99%
“…The altered synaptic inputs may also cause a more general effect, which is a widespread alteration of the excitation/inhibition (E/I) balance. E/I imbalance is regarded as a key pathogenic mechanism in numerous neurodevelopmental disorders (Deidda et al, 2015;Kim et al, 2021). Thus, it is possible that through recurrent inhibitory and excitatory circuitries the mPFC network acts as a magnifier of the effects of even minor alterations in specific inputs, so that relatively minor synaptic changes end up producing large behavioral effects.…”
Section: Discussionmentioning
confidence: 99%
“…In the subchronic phencyclidine (scPCP)-treated mice, a well-studied animal model mimicking the cognitive impairment symptoms associated with schizophrenia (Jentsch and Roth, 1999 ; Steeds et al, 2015 ; Kim et al, 2021 ) found that the reversal potential of GABA (E GABA ) recorded from pyramidal neurons in the infralimbic cortex (the more ventral portion of the prefrontal cortex) was more positive in scPCP-treated mice as compared to those treated with vehicle. This effect was highly specific since it was not found in the prelimbic cortex, which is also part of the prefrontal cortex and sits just above the infralimbic cortex.…”
Section: Schizophreniamentioning
confidence: 99%
“…Thus, recent investigations hypothesized that bumetanide levels in the brain after systemic administration were not sufficient to cause NKCC1 inhibition, calling into question whether brain-expressed NKCC1 is the effector of the action of bumetanide in neurological disorders [117,118] (see Outstanding questions). However, RNAi-based experiments with downregulation of endogenous NKCC1 led to rescue of core symptoms in rodent models of four diverse neurological conditions, validating NKCC1 as a factual effector and, thus, as a pharmacological target in brain diseases [8][9][10][11][12]. In addition, despite its low brain penetration, bumetanide efficacy should be assessed by taking into consideration the low [Cl -] i variations (and so a likely low level of NKCC1 inhibition) necessary to affect neuronal excitability [119] (Box 1).…”
Section: Drawbacks Of Bumetanidementioning
confidence: 98%
“…Several NDs are characterized by cognitive impairment (deficits in memory, attention, and cognitive flexibility), including DS (a genetic disorder caused by triplication of chromosome 21), schizophrenia (a psychiatric disorder the cause of which is not completely understood), and fetal alcohol spectrum disorders (FASD) (a group of conditions caused by prenatal alcohol exposure). NKCC1 upregulation was reported in adult Ts65Dn mice, a model of DS [39], and in scPCP mice, a model of schizophrenia [8] (Table 1). Bumetanide ameliorated cognitive impairments in these two models [8,39] (Table 2).…”
Section: Trends In Pharmacological Sciencesmentioning
confidence: 99%
See 1 more Smart Citation